2020
DOI: 10.1115/1.4047755
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Operational Planning Tool for Geothermal Plants With Heat and Power Production

Abstract: Abstract A short-term operational planning tool for geothermal plants with heat and power production connected to large district heating systems is developed. The software tool contains, among other features, a heat demand forecasting model for district heating systems. Two options, such as linear regression and artificial neural networks, are compared. As the result shows, artificial neural networks with the Bayesian Regularization Backpropagation Algorithm have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In the existing research on the impact of new energy participation on the electricity spot market, it has been confirmed that the priority effect of new energy causes the price of electricity market clearing to drop, but the impact of new energy participation on the electricity spot market price still lacks a comprehensive method system. In addition, there is a lack of a quantitative model for the impact of new energy on the spot market price of electricity, and it is impossible to transfer the impact of new energy to the electricity price in the spot market [16][17].…”
Section: Key Issues Of Constructionmentioning
confidence: 99%
“…In the existing research on the impact of new energy participation on the electricity spot market, it has been confirmed that the priority effect of new energy causes the price of electricity market clearing to drop, but the impact of new energy participation on the electricity spot market price still lacks a comprehensive method system. In addition, there is a lack of a quantitative model for the impact of new energy on the spot market price of electricity, and it is impossible to transfer the impact of new energy to the electricity price in the spot market [16][17].…”
Section: Key Issues Of Constructionmentioning
confidence: 99%